LATE YEARS OF PROFESSOR M. RÖMERIS - Maksimaitis, Mindaugas (Teisė, 2017)
This article covers the last five years of Professor’s M. Römeris life, coincided with several occupations of Lithuania, which followed one after another during the Second World War. These last five years were marked with major changes of living conditions that lead to distancing himself not only from active public and social activities, but also from usual academic work.